Web-Based Motorcycle Rental System Design - Jama Toyo; Putri Yapono (CV Edujavare Publishing, 2026)
The development of information technology has encouraged many businesses to switch to a more effective and efficient system, including in the business world, especially in vehicle rental. This research aims to discuss the design of a web-based motorcycle rental rental system that aims to simplify the ordering process, data management, and service to customers. The system is designed to provide features for online motorcycle booking, customer data management, motorcycle availability management, and automatic transaction recording. The research method with a qualitative approach with three data collection techniques, namely, Literature Study, Observation and Interview. System development methods include needs analysis, interface design, and implementation using web technology. The results of the study show that with this system, the rental process becomes faster, transparent, and structured so that it can improve operational efficiency and service quality in the motorcycle rental business.